Improving the Efficiency of Oil and Gas Asset Handling in the Receiving Process at an Oil & Gas Logistics Company - Yunanik; Brian Lodowig Leiksyoru Manaha; Dwi Nurma Heitasari (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2026)
Warehouses play a strategic role in the oil and gas logistics industry, particularly in the receiving process as the initial stage of asset management. This study was conducted at the Oil & Gas Logistics Co. warehouse to identify and reduce non-value-added activities (waste) through the implementation of a Lean Service approach. The analysis examined the proportions of Value-Added (VA), Non-Value-Added (NVA), and Necessary but Non-Value-Added (NNVA) activities, and proposed improvements aimed at enhancing process efficiency and warehouse performance. The methods employed included Value Stream Mapping (VSM), a Seven Waste questionnaire, Value Stream Analysis Tools (VALSAT), Process Activity Mapping (PAM), and Root Cause Analysis (RCA) using a fishbone diagram. The results indicated that the dominant waste in the receiving process was due to waiting/delays (21%) and overprocessing (19%). The implementation of Lean Service reduced lead time from 1,173.78 minutes to 1,018.50 minutes (approximately a 13% efficiency improvement) and decreased the proportion of NVA from 12.14% to 3.22%. This reduction of 155.28 minutes per cycle corresponded to labor cost savings of approximately Rp128,706 per cycle. Overall, the implementation of Lean Service improves operational efficiency, supports the achievement of warehouse KPIs, and provides significant economic benefits with a high Return on Investment (ROI), making it a potential model for continuous improvement in oil and gas logistics as well as other logistics sectors.